Introducing Patient Cards in Clinical Routine: Evaluation of Two Research Projects - Birkmann, C.; Demski, H.; Engelbrecht, R. (Methods of Information in Medicine, 2006)
Objective: Two research projects were analyzed in order to identify key factors of success and/or failure in introducing patient card-based systems in clinical routine.Methods: In DIABCARD an evaluation study focussing on user friendliness and user acceptance was conducted. In ByMedCard-HCPP the project’s system was validated and the timeliness of the project’s work analyzed.Results: User friendliness and user acceptance of the DIABCARD system were fairly high. The ByMedCard-HCPP system was complete in its major components and functionalities; introducing the ByMedCard-HCPP system in clinical routine delayed the project.Conclusions: A multitude of key factors of success such as utilized technologies, user involvement, and commitment of partners seems to contribute to the success and/or failure of introducing patient card-based systems in healthcare.
Keywords: Patient data card; health professional card; electronic health record; success factors; Internet